PEREMPUAN DAN KETIDAKADILAN GENDER (Studi Kasus Bentuk-Bentuk Ketidakadilan Gender di Kota Kendari Tahun 2024) - Iriyani Astuti Arief; Indra Lestari; Muh.Ishak Syahadat; La Ode Efrianto (Halu Oleo University, 2024)
The purpose of this research is to identify and examine gender inequality as a manifestation of gender differences in Kendari City in 2024. It will examine the forms of gender inequality that women in Kendari City face using the gender concept. The research method used is mixed methods, which combine qualitative and quantitative research methodologies. Data collection techniques using questionnaires distributed via Google form, literature study, and documentation. The three steps of the analysis technique are data reduction, data display, and conclusion drawing. The research indicates that there are five forms of gender inequality in Kendari City, namely: Marginalization, Subordination, Stereotypes, Violence and Workload. Stereotypes, Marginalization, and Subordination are less dominant than the most dominant form of violence that women in Kendari City face. Based on data from the Women’s Empowerment and Child Protection Service, there were 26 cases of violence against women that occurred in the workplace, public spaces, and at home. The workload was found to be 44.4%, especially for women who act as both breadwinners and housewives. In conclusion, workload and violence are the most prevalent forms of gender inequality in Kendari City. Poor economic conditions are the primary factor of this violence and workload.